Research on sedimentary facies of Guantao Formation in Shanjiasi area of Dongying depression, China. (November 2021) - Cheng, Zijian; Xu, Haoli; Wang, Daqing; Zhang, Liqiang; Shi, Yue; Lu, Zhao; Zhao, Xiaoning
Abstract: Alluvial fan and Fluvial facies sand bodies are important reservoirs for oil and gas resources. In this study, the sedimentary characteristics and evolutionary patterns of Alluvial fan and fluvial deposits in the Neogene Guantao Formation of the Dongying Sag, Bohai Bay Basin were analyzed using cores, well logs and three-dimensional seismic data, and the quantitative information of the sand bodies in different deposits were characterized with dense well-net constraints. Through the calibration between the core and wireline logging data, the developmental characteristics of the sand bodies in the Alluvial fan and fluvial deposits were clearly defined base on sedimentary microfacies and seismic facies interpretation. Using the RMS amplitude attribute and reconstructed Wave Impedance Inversion, the sand bodies of Guantao Formation in this area were carefully described and studied, and the effective reservoir range was predicted on the basis of fully understanding the oil test data. Results: The top and bottom interface of Guantao Formation are characterized by strong continuous reflection on seismic section, exist within the guantao on seismic section three continuous or intermittent peaks, from bottom to top respectively represent the interface between Ng4 and Ng3 sand group, the interface between Ng3 and Ng2 sand group, the interface between Ng2 and Ng1 of the Guantao Formation, and Ng4 sand group of the Guantao Formation is the key layer; The boundary Growth Fault and Binxian high jointly controlled the deposition of Guantao Formation. The sedimentary thickness of the strata decreased on the north and west sides of the sag, and increased from the core to the edge of the Binxian high; The sedimentary facies of Guantao Formation in the study area can be divided into three types: alluvial fan facies, braided river facies and meandering river facies, and various corresponding subfacies and microfacies can be subdivided into different types. Ng4 sand group of the Guantao Formation is identified as alluvial fan-braided river model; Based on the analysis of the distribution and physical properties of alluvial and fluvial facies sand bodies in the study area, it is considered that the effective reservoir of Ng4 sand group of the Guantao Formation is mainly developed in the nose structure around Binxian high, and is semicircular in distribution.